Nutritional regulation of long-chain PUFA biosynthetic genes in rainbow trout (Oncorhynchus mykiss) - MK Gregory; RO Collins; DR Tocher; MJ James; GM Turchini (2016)
AbstractMost studies on dietary vegetable oil in rainbow trout (Oncorhynchus mykiss) have been conducted on a background of dietary EPA (20 : 5n-3) and DHA (22 : 6n-3) contained in the fishmeal used as a protein source in aquaculture feed. If dietary EPA and DHA repress their endogenous synthesis fromα-linolenic acid (ALA, 18 : 3n-3), then the potential of ALA-containing vegetable oils to maintain tissue EPA and DHA has been underestimated. We examined the effect of individual dietaryn-3 PUFA on the expression of the biosynthetic genes required for metabolism of ALA to DHA in rainbow trout. A total of 720 juvenile rainbow trout were allocated to twenty-four experimental tanks and assigned one of eight diets. The effect of dietary ALA, EPA or DHA, in isolation or in combination, on hepatic expression of fatty acyl desaturase (FADS)2a(Δ6),FADS2b(Δ5), elongation of very long-chain fatty acid (ELOVL)5andELOVL2was examined after 3 weeks of dietary intervention. The effect of these diets on liver and muscle phospholipid PUFA composition was also examined. The expression levels ofFADS2a(Δ6), ELOVL5andELOVL2were highest when diets were high in ALA, with no added EPA or DHA. Under these conditions ALA was readily converted to tissue DHA. Dietary DHA had the largest and most consistent effect in down-regulating the gene expression of all four genes. TheELOVL5expression was the least responsive of the four genes to dietaryn-3 PUFA changes. These findings should be considered when optimising aquaculture feeds containing vegetable oils and/or fish oil or fishmeal to achieve maximum DHA synthesis.